2018
DOI: 10.1111/joim.12718
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of bone marrow adiposity

Abstract: Abstract. Veldhuis-Vlug AG, Rosen CJ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
149
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(154 citation statements)
references
References 152 publications
3
149
0
2
Order By: Relevance
“…RANK is located in the cell membrane of osteoclasts and facilitates osteoclast activation and differentiation . RANKL was declared to accelerate bone resorption and depression of NF‐κB pathway represses osteoclast differentiation . All the above demonstrations provided evidence that the NF‐κB pathway plays an important role in OP progression and makes simulative effects on bone resorption and activation of OP.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…RANK is located in the cell membrane of osteoclasts and facilitates osteoclast activation and differentiation . RANKL was declared to accelerate bone resorption and depression of NF‐κB pathway represses osteoclast differentiation . All the above demonstrations provided evidence that the NF‐κB pathway plays an important role in OP progression and makes simulative effects on bone resorption and activation of OP.…”
Section: Discussionmentioning
confidence: 90%
“…3 RANKL was declared to accelerate bone resorption and depression of NF-κB pathway represses osteoclast differentiation. 36,37 All the above demonstrations provided evidence that the NF-κB pathway plays an important role in OP progression and makes simulative effects on bone resorption and activation of OP. In the present study, we found that the NF-κB pathway could be inhibited by CST5 up-regulation and by which mechanism the progression of OP was impeded.…”
Section: Discussionmentioning
confidence: 90%
“…T HE PROPORTION of bone marrow adipose tissue is thought to be related to the strength and remodeling capacity of the bone, 1 and quantitative changes in the bone marrow fat fraction have been examined in various pathologic states: first, bone marrow adiposity has been found to correlate with the bone loss pathophysiology in the course of osteoporosis and to increase the fracture risk in metabolic diseases such as diabetes mellitus. 2 Second, bone marrow adipose tissue has been shown to be replaced by malignant bone marrow processes, potentially providing a diagnostic instrument for the differentiation of benign and malignant bone marrow lesions. [3][4][5] Third, increased bone marrow fat fractions have been observed in patients with malignant disease and a positive treatment response to both chemotherapy and radiation.…”
mentioning
confidence: 99%
“…It is likely that multiple body‐weight‐related alterations in metabolism are involved, including changes to the bone marrow microenvironment (Askmyr et al , ). Adipocytes are one of the most abundant cell types in bone marrow, and animal and in vitro studies suggest that bone marrow adipocytes may play a direct, active role in supporting leukemogenesis (Veldhuis‐Vlug & Rosen, ).…”
Section: Discussionmentioning
confidence: 99%